Automation and Employment over the Technology Life Cycle: Evidence from European Regions - Florencia Jaccoud; Fabien Petit; Tommaso Ciarli; Maria Savona (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper examines the labor market implications of investment in automation over the life cycle of ICT and robot technologies from 1995 to 2017 in 163 European regions. We first identify major technological breakthroughs during this period for these automation technologies and identify the phases of acceleration and deceleration in investment. We then examine how exposure to these automation technologies affects employment and wages across these different phases of their life cycle. We find that the negligible long term impact of automation on employment conceals significant short term positive and negative effects within phases of the technology life cycle. We also find that the negative impact of ICT investment on employment is driven by the phase of the cycle when investment decelerates (and the technology is more mature). The phases of the technology life cycles are more relevant than differences in regions' structural characteristics, such as productivity and sector specialization in explaining the impact of automation on regional employment.
Keywords: J21; O33; J31; 330; automation; technology life cycle; employment; wages; ICT; robot